Kebudayaan Dalam Persepsi Islam - Zaenal Abidin; Risal Qori Amarullah; Isop Syafei; Edy (Edusifa: Jurnal Pendidikan Islam, 2024)
This study aims to analyze culture in Islamic perceptions. This research is important because of the rise of cultures circulating in society. This research provides important insights regarding how culture is perceived in Islam, so that the habits or behavior carried out by the community are not only cultural but must be based on the Al-Qur'an and the Sunnah of the Prophet Muhammad. In writing this journal the authors used the method of library research (library research), then analyzed using the method of content analysis (content analysis) in the form of descriptive-analytic by collecting data from literature related to discussions of culture in Islamic perceptions. The results of this study the authors found the answer that culture in Islamic perception is a manifestation of the results of human reason or morality and rationality which are then transformed into a reality of social order, Islamic culture has two aspects, namely the normative aspect and the application aspect, the normative aspect is the main source based on the Al-Qur'an 'an and the Sunnah of Rasulullah SAW, while the implementation aspect is the actualization which is carried out based on the Al-Qur'an and Sunnah of Rasulullah SAW Keywords: Culture, Perception, Islam